2009
DOI: 10.1590/s1677-55382009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of open radical prostatectomy versus laparoscopic radical prostatectomy in Asian men: comparison of two initial series by the same surgeon

Abstract: Purpose: To compare the perioperative outcomes in 2 initial series of open radical prostatectomy (ORP) and laparoscopic radical prostatectomy (LRP) in Asian men with prostate cancer. Materials and Methods: From March 1999 to February 2007, the first 100 consecutive patients who underwent ORP and the first 100 consecutive patients who underwent LRP by the same surgeon (SL) were assessed. Mean age, clinical stage, preoperative PSA level, Gleason score, operative time, estimated blood loss, blood transfusion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Meanwhile, LRP has been reported to have decreased blood loss and decreased need for blood transfusion, but also extends operative time. 99 Furthermore, robot-assisted LRP is a new option that has been widely used in America and many parts of Europe, though it is in its infancy in Asia. Until 2009, only eight regions had a robot system; in total there were 24 systems in Asian countries, namely in the mainland of China, South Korea, Japan, Taiwan (China), India, Thailand, Singapore and Malaysia.…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%
“…Meanwhile, LRP has been reported to have decreased blood loss and decreased need for blood transfusion, but also extends operative time. 99 Furthermore, robot-assisted LRP is a new option that has been widely used in America and many parts of Europe, though it is in its infancy in Asia. Until 2009, only eight regions had a robot system; in total there were 24 systems in Asian countries, namely in the mainland of China, South Korea, Japan, Taiwan (China), India, Thailand, Singapore and Malaysia.…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%
“…It was concluded that the RARP provided a shorter catheter time (76,77). A routine cystography at Post-operative day 7 was not found to be necessary following an operation involving the extraperitoneal approach in either a laparoscopic radical prostatectomy or a robot-assisted radical prostatectomy (75).…”
Section: Prostate Cancermentioning
confidence: 99%
“…[1] Prostatectomy using Da Vinci robot has many advantages like less bleeding, less postoperative pain, shorter hospital stay, and quick recovery. [2,3] It also reduces complications including urinary incontinence and impotence. [4] However, RALRP needs prolonged pneumoperitoneum and steep Trendelenburg position over 30° for surgical exposure.…”
Section: Introductionmentioning
confidence: 99%